PJMHS 2022
DOI: 10.53350/pjmhs22167169
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Indications and Outcome of Emergency Obstetric Hysterectomy: A study performed at Tertiary Care Hospital

Abstract: Background: Emergency obstetric hysterectomy is the life-saving surgical intervention when all other available measures are unable to control obstetric hemorrhage. In addition to the known indications and risk factors for globally increasing this near miss event, home deliveries by untrained birth attendants is irrefutable cause of obstetric morbidity and mortality Aim: To identify the risk factors and indications for EOH like Pakistan. Study design: Retrospective descriptive study. Settings: OB/GYN depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…While Dani A et al 3 found that 84.6% of patients had a history of multiparity. Similar results were seen in a study done by Aslam L. et al 5 reported that 79.16% were multipara in their study. The majority (88%) of the patients have registered ANC cases while the remaining 12% were unbooked & were referred late from the peripheral health care centers.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While Dani A et al 3 found that 84.6% of patients had a history of multiparity. Similar results were seen in a study done by Aslam L. et al 5 reported that 79.16% were multipara in their study. The majority (88%) of the patients have registered ANC cases while the remaining 12% were unbooked & were referred late from the peripheral health care centers.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found an incidence of 8 per 1000 deliveries. Similar results were reported in a study conducted by Aslam L. et al 5 7.05 per 1000 deliveries. While results in our study are in contrast with studies conducted by Dogra A. et al 1 it was 1.32 per 1000 deliveries, also Rana S. et al 2 reported 0.2 per 1000 deliveries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations